2003
DOI: 10.1212/wnl.61.5.716
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to solvents and metals and Parkinson’s disease

Abstract: Objectives: To investigate associations between occupational exposure to solvents and metals and fixed airflow obstruction using post-bronchodilator spirometry. Methods: From 1,335 participants in the 2002-2008 follow-up of the Tasmanian Longitudinal Health Study (TAHS) cohort who completed lung function testing and lifetime work history calendars. Ever exposure and cumulative-exposure-unit-years were calculated using the ALOHA+Job Exposure Matrix. Fixed AO was defined by post-bronchodilator FEV 1 / FVC<0.7 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 6 publications
2
21
1
Order By: Relevance
“…Six other case-control studies, including the large (767 cases) European multicentre study [300], observed no association between organic solvents and PD [300,308,310,313,317,393]. One case-control study found an increased risk with longer duration of exposure (OR 3.59, 95% CI 1.26-19.26 for 20-30 years of exposure versus not exposed, p for trend 0.04) although no association was observed overall [381].…”
Section: Organic Solventsmentioning
confidence: 97%
See 1 more Smart Citation
“…Six other case-control studies, including the large (767 cases) European multicentre study [300], observed no association between organic solvents and PD [300,308,310,313,317,393]. One case-control study found an increased risk with longer duration of exposure (OR 3.59, 95% CI 1.26-19.26 for 20-30 years of exposure versus not exposed, p for trend 0.04) although no association was observed overall [381].…”
Section: Organic Solventsmentioning
confidence: 97%
“…Some studies assessed metal exposure overall through questionnaires without collecting information on occupational history, an approach that also captures recreational metal exposure. Of studies that examined exposure to heavy metals overall, only one reported an increased risk (OR11.84, 95% CI 1.08-130.37) [358], whereas the others found no association [293,313,381]. Another study found no association for residential proximity to steel plants [146].…”
Section: Metalsmentioning
confidence: 99%
“…Several studies have suggested that exposures to aluminum, copper, and lead are risk factors for PD, 10,73,74 but no such link has been found for manganese. 10,12,[74][75][76][77][78][79][80] In one study conducted in southern Quebec (Canada), involving 42 parkinsonian patients compared with a group of 84 matched controls, a slightly increased risk for PD was found to be associated with occupational exposure to manganese, iron, and aluminum, but this association did not reach statistical significance. 81 In a study of WWII Twins Cohort, involving 163 twin pairs, in which a blinded industrial hygienist estimated lifetime occupational manganese exposure intensity and duration, twins with PD were less likely to have ever been exposed to manganese than their control twin (OR ϭ 0.36) and had a shorter average duration of manganese exposure than did controls.…”
Section: How Is the Diagnosis Of Manganese-induced Parkinsonism Confimentioning
confidence: 99%
“…Although several studies found associations with self-reported solvent exposures [17][18][19], several large methodologically rigorous studies have found no association. Indeed, the performance of tasks likely to involve solvent exposure was not associated with PD in a study using custom task-based interviews [20], or in another that included a job-exposure matrix and industrial-hygienist review to impute lifetime solvent exposures [21].…”
mentioning
confidence: 98%